4.8k views
5 votes
2x^2-3x-14


Please show some work

1 Answer

1 vote

Answer:

(x+2)(2x−7)

Explanation:

For a polynomial of the form ax2+bx+cax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=2⋅−14=−28a⋅c=2⋅-14=-28 and whose sum is b=−3b=-3.

2x2+4x−7x−142x2+4x-7x-14

Factor out the greatest common factor from each group.

2x(x+2)−7(x+2)2x(x+2)-7(x+2)

Factor the polynomial by factoring out the greatest common factor, x+2x+2.

(x+2)(2x−7)

hope this helps

User HotIceCream
by
4.2k points